2010
DOI: 10.2174/157015910792246164
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Metabolism in the Central Nervous System

Abstract: Abstract:The metabolism of melatonin in the central nervous system is of interest for several reasons. Melatonin enters the brain either via the pineal recess or by uptake from the blood. It has been assumed to be also formed in some brain areas. Neuroprotection by melatonin has been demonstrated in numerous model systems, and various attempts have been undertaken to counteract neurodegeneration by melatonin treatment. Several concurrent pathways lead to different products. Cytochrome P 450 subforms have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 141 publications
(246 reference statements)
2
110
0
Order By: Relevance
“…It has been documented that serum melatonin concentrations (43) and pineal AANAT activity (44) decrease during aging. Rat pineal and hippocampal AANAT expression decreases in old age (45,46). In extrapineal tissues (liver, spleen, and heart), it has been shown that the melatonin concentration, enzymatic activity, and the gene expression of HIOMT decrease during aging without specific changes in AANAT or significant alterations in its concentration and enzymatic activity in the rat thymus (47).…”
Section: Melatonin During Agingmentioning
confidence: 99%
“…It has been documented that serum melatonin concentrations (43) and pineal AANAT activity (44) decrease during aging. Rat pineal and hippocampal AANAT expression decreases in old age (45,46). In extrapineal tissues (liver, spleen, and heart), it has been shown that the melatonin concentration, enzymatic activity, and the gene expression of HIOMT decrease during aging without specific changes in AANAT or significant alterations in its concentration and enzymatic activity in the rat thymus (47).…”
Section: Melatonin During Agingmentioning
confidence: 99%
“…In contrast with melatonin, both 5-MT and serotonin are rapidly metabolized MAO substrates, the enzyme 450 Haduch et al at ASPET Journals on May 11, 2018 dmd.aspetjournals.org being present in a large amount in the liver and brain (Suzuki et al, 1981;Galzin and Langer, 1986;Raynaud and Pévet, 1991;Hardeland, 2010). However, the effect of melatonin on serotonin level is not visible in the majority of structures of the pargyline-pretreated, nonlesioned animals (both controls and sham-operated), since the amount of the tissue serotonin synthesized physiologically from endogenous substrates (mainly from tryptophan, but also from endogenous 5-MT) and protected from MAO probably largely dominates the serotonin formed indirectly from exogenous melatonin (via melatonin deacetylation to 5-MT and subsequent O-demethylation by CYP2D).…”
Section: Discussionmentioning
confidence: 99%
“…Being an amphiphilic substance, peripheral melatonin easily crosses the blood-brain barrier (Green et al, 1975). Circulating melatonin is metabolized mainly in the liver by cytochrome P450 isoforms of the CYP1A subfamily (CYP1A1/A2/B1) to form 6-hydroxymelatonin and then 6-sulfatoxymelatonin (Ma et al, 2005;Hardeland, 2010), but it can also be deacetylated to 5-methoxytryptamine (5-MT) (Rogawski et al, 1979;Beck and Jonsson, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin is deacetylated, at least in pineal gland and retina, to 5-methoxytryptamine. Many of the melatonin metabolites, which may appear in elevated concentrations after melatonin administration, possess biological or pharmacological properties, including N-acetylserotonin, 5-methoxytryptamine and some of its derivatives, and especially the 5-methoxylated kynuramines (26,27). Rat mitochondrial CYP 2C6 and 3A has also been associated with melatonin metabolism (24).…”
Section: Introductionmentioning
confidence: 99%